The Influence of Different Blending Materials on the Hydration Activity of High Belite Clinker and Its Mechanism Exploration - Yang, Renhe; Zhang, Pengyu; Li, Jiaqi; Huang, Tianyong; Wang, Dongmei; Sun, Qian; Liang, Zengyun; Xu, Rongsheng; Da, Yongqi (Langmuir, 2025)
Improving the performance of a high belite clinker (HBC) by selecting appropriate blended materials is of great significance for its large-scale promotion and application. This research attempted to use dihydrate gypsum (DGP), fly ash (FA), and ground granulated blast furnace slag (GGBS) to prepare HBC + DGP (95% HBC + 5% DGP), HBC + FA (82% HBC + 3% DGP + 15% FA), and HBC + GGBS (82% HBC + 3% DGP + 15% GGBS) and explored the influence of different blended materials on various properties of HBC. In addition, the mechanism of the interaction between HBC and different blended materials in early and late stages was also revealed. The experimental results showed that GGBS had the most significant impact on HBC, mainly manifested in optimizing the particle distribution of HBC, increasing the standard consistency water demand of HBC, and shortening the setting time of the HBC paste. The improvement of the mechanical property of HBC by GGBS was its main advantage. Compared with HBC + DGP, the compressive strength of HBC + GGBS mortar increased by 113.9% and 43.5% at 7 and 28d, respectively. It was found that the addition of GGBS could increase the HBC second hydration exothermic peak to 15.4 mW/g. Further analysis proved that in the early stage, strong polarity OH– could dissociate the Ca–O and Si–O bonds on the glass phase of the GGBS surface, and the released Ca2+and SiO3 2– combined to form CH and C–S–H nanocrystalline nuclei, which could reduce the nucleation barrier of CH crystal and effectively promote C3S acceleration reaction. In the hydration later stage, the pozzolanic effect was utilized to generate more C–S–H, which could fill the pore of the cement matrix. This further enhanced the compressive strength of the HBC + GGBS mortar.